2010
DOI: 10.1063/1.3436598
|View full text |Cite
|
Sign up to set email alerts
|

Channel strain analysis in high-performance damascene-gate p-metal-oxide-semiconductor field effect transistors using high-spatial resolution Raman spectroscopy

Abstract: Channel strain analysis in damascene-gate p-metal-oxide-semiconductor field effect transistors (pMOSFETs) with a compressive stress liner and embedded SiGe after the dummy gate removal was studied using micro-Raman spectroscopy with a UV laser (λ=363.8 nm) and a quasiline excitation source. Using a quasiline excitation source, we obtained spatial and energy information simultaneously with a high spatial resolution in the one-dimensional strain profile. For Lgate>210 nm samples, we performed laser exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…Comparing the results of the Raman measurements with the conventional and oil immersion lenses in Figures 4 and 5, the stress enhancement at the SiN film edges is clearer in the oil immersion Raman method than in the conventional Raman method. Furthermore, it was observed that the strain induced in the space region increases with reducing space width, specifically in the oil immersion Raman measurement, which confirms the strain-size effect as was observed in previous studies [20,21]. As a result, the beam spot sizes were determined to be 750 and 350 nm in conventional and oil immersion Raman spectroscopy, respectively, obtained by comparing the measured data and the EFM calculations with the correction of optical penetration depth and beam spot size.…”
Section: Methods Of Stress/strainsupporting
confidence: 88%
“…Comparing the results of the Raman measurements with the conventional and oil immersion lenses in Figures 4 and 5, the stress enhancement at the SiN film edges is clearer in the oil immersion Raman method than in the conventional Raman method. Furthermore, it was observed that the strain induced in the space region increases with reducing space width, specifically in the oil immersion Raman measurement, which confirms the strain-size effect as was observed in previous studies [20,21]. As a result, the beam spot sizes were determined to be 750 and 350 nm in conventional and oil immersion Raman spectroscopy, respectively, obtained by comparing the measured data and the EFM calculations with the correction of optical penetration depth and beam spot size.…”
Section: Methods Of Stress/strainsupporting
confidence: 88%
“…The SERS technique is suitable for strain (stress) measurements on extremely miniaturized transistors. In our previous study, stress measurements in n‐ and p‐type 30‐nm‐channel transistors were performed by UV‐Raman spectroscopy . However, long exposure time was needed to detect stresses in areas of several tens of nanometers using conventional Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Raman spectroscopy has the advantages such as high sensitive to local strain, submicron spatial resolution, nondestructive measurements, fast measurements, and ease of use. Consequently, Raman spectroscopy has been frequently used by many researchers to measure the strain in Si [3,[7][8][9][17][18][19][20][21]. However, conventional Raman spectroscopy fails to measure the complicated stress states in Si.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, the strain is induced only in the desired region, the channel region of FET [7,8]. A SiN film is used as the stressor that can induce tensile or compressive uniaxial stress in Si by changing the deposition conditions of the SiN film [9,10].…”
Section: Introductionmentioning
confidence: 99%